Discourse analysis of teachers on formation by competences and appropriation in the curriculum in Faculty of Odontology of the Universidad Nacional de Colombia - Julián Alfonso Orjuela Benavides; John Harold Estrada Montoya (Universidad Nacional de Colombia, 2013)
Introduction: This research is exploratory, descriptive and qualitative, which aims to determine the types of discourses on skills training and ownership by the teachers in the curriculum of the Faculty of Odontology of the Universidad Nacional de Colombia-Bogota. Methods: A literature review was performed, and then there were eight (8) Interviews: four (4) experts, three (3) teachers dedicated exclusively to teaching and one (1) teacher with administrative fee. As a third step the Triangulation and preliminary analysis of the information, finally Debugging and definitive analysis of the information. Results: For this approach the discussion in 4 stages: Capitalism and skills training that reveals the ideological background of the approach, the second competency-based training in Colombia, placing the development and incorporation into the curricula, the third moment is called rationales underlying skills training, and finally analyze the process at the Faculty of Dentistry. Conclusions: As a corollary performed a series of reflections and recommendations to advance a democratic educational project, pluralistic, critical and autonomous in the Faculty of Dentistry at the National University of Colombia.